SUNE BECHMANN PEDERSEN, Reel Socialism. Making Sense of History in Czech and German cinema since 1989: Lund 2015, Lund University Press, 326 s. - Pýcha, Čeněk (Dějiny – teorie – kritika, 2017)
Review.